Social accountability in local government: Lessons from Vuwani (South Africa) and Gweru (Zimbabwe) - Kanyane, Modimowabarwa; Mutema, Edson P.; Zikhali, Thobekile (John Wiley and Sons Ltd, 2021)
What do experiences in South Africa and Zimbabwe teach us about the relationship between social accountability and public participation? The relationship between social accountability and public participation is widely acknowledged as important, yet the nuances that inform such a relationship are not critically discussed. To understand such nuances, this paper critically engages two cases: Vuwani (South Africa) and Gweru (Zimbabwe). The study underscores the importance of social accountability and public participation in local governance. Robust and open citizen engagement is critical to hold the state accountable. Thus, the two cases show how lack of a constructive participatory framework, wherein all relevant stakeholders are given a voice and informed about all developments, is problematic and can cause destructive outcomes in one case and sustained political frustrations in another. Using interviews with various social actors, document analysis and observations to bring to the fore social accountability and public participation nuances, this paper argues that public participation applies in different contexts and forms part of social accountability initiatives which largely depend on the extent of public engagement with non-state actors.